Drawing Clocks without Time: Alzheimer’s, Marginalization, and the Liberatory Potential of Object Memoir - Howarth, Lynne (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2016)
Dementia and Alzheimer’s disease know no boundaries. While this much is known, there is little beyond the medicalization of onset to provide insights into individuals instantly marginalized by a diagnosis with no future. How can surrogates and object memoir be mobilized to empower the voices of the cognitively disabled? La démence et la maladie d'Alzheimer ne connaissent pas de limites, nous savons cela, mais outre la médicalisation lors d’une attaque, nous avons peu d’éléments susceptibles de nous fournir des indications sur des personnes instantanément marginalisées par un diagnostic qui bloque tout avenir. Comment les substituts et les mémoires d’objet peuvent être mis à profit pour habiliter les voix des personnes cognitivement handicapées ?